Development of a method and an apparatus for tribotechnical tests of materials under loose abrasive friction - Lutsak, Dmytro; Prysyazhnyuk, Pavlo; Burda, Myroslav; Aulin, Viktor (Eastern-European Journal of Enterprise Technologies, 2016)
We have developed a method and an apparatus for determining the relative wear resistance of materials under conditions of friction on a loose abrasive. The study suggests an algorithm for calculating geometric parameters of abrasive particles, which makes it possible to present the contours of abrasive particles, used to determine the wear resistance, as functions and to calculate the sharpness parameter of particles SPLm, which is in close correlation with the intensity of wear for abrasives of various shapes. This technique was used to analyze the geometric parameters of selected abrasive particles before and after the tests by the Lorentz force method and after the tests on the developed apparatus. A regression analysis has resulted in an equation that determines a correlation between the wear intensity for steel and the parameters of the abrasive particle’s sharpness SPLm, roundness R, convexity C, and size (Fmax). The suggested method and apparatus for determining the relative wear resistance of materials under conditions of friction on a loose abrasive improve the efficiency of tribotechnical testing by allowing testing of materials for wear by a loose abrasive at a significant specific pressure of the abrasive and at a high degree of exchange in the abrasive mass in the area of interaction between the working surface of the sample and the abrasive, which increases the ability of abrasive silicon carbide particles ~1.4 times compared to the Lorentz force method.